2019
DOI: 10.30738/mmp.v2i1.3180
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Sekolah Dasar Berwawasan Lingkungan Hidup

Abstract: Penelitian ini bertujuan untuk mengidentifikasi berbagai hambatan dalam implementasi manajemen Pembelajaran Lingkungan Hidup (PLH) di Sekolah Dasar Kanisius Daerah Istimewa Yogyakarta. Metode dalam penelitian ini menggunakan metode kualitatif, sumber datanya terdiri dari sumber daya manusia yang ada di lokasi penelitian, sumber data berupa tempat, dan sumber data dokumen. Teknik pengumpulan datanya menggunakan teknik observasi, wawancara, dan dokumentasi. Sementara itu, untuk menguji keabsahan datanya mengguna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…In the JN9 article it was found that there are 3 main strategies that the government must carry out to achieve the development of halal tourism, namely: 1) marketing development; 2) destination development; and 3) industrial and institutional development (Sayekti, 2019). So, the government has three key strategies that must be implemented to achieve halal tourism development.…”
Section: Resultsmentioning
confidence: 99%
“…In the JN9 article it was found that there are 3 main strategies that the government must carry out to achieve the development of halal tourism, namely: 1) marketing development; 2) destination development; and 3) industrial and institutional development (Sayekti, 2019). So, the government has three key strategies that must be implemented to achieve halal tourism development.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study are in line with the theory of ecotourism which explains that ecotourism is a type of environmentally sound tourism. It means that through activities related to nature, tourists are invited to see nature up close, enjoy the authenticity of nature and its environment, so that it inspires them to love nature (Yoeti, 2000). Ecotourism activities can increase revenue for nature conservation which is used as an ecotourism tourism object and generate economic benefits for the lives of the people who live in the area or the local area (Subadra, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sekolah berwawasan lingkungan (SBL) adalah suatu program pemerintah dimana sekolah merupakan ujung tombak yang dapat membentuk generasi yang akan dating dan mampu sadar akan pelestarian lingkungan, tercapainya kemampuan nasional dalam pemanfaatan, pengembangan dan pengusaan ilmu pengetahuan dan teknologi yang dibutuhkan bagi peningkatan kesejahteraan, kemajuan peradaban, serta ketangguhan dan daya saing bangsa yang diperlukan untuk memacu pembangunan yang berkelanjutan dan berwawasan lingkungan (Sayekti, 2019).…”
Section: Tinjuan Pustakaunclassified